Labour Market in Motion - Analysing Regional Flows in a Multi-Account System - Anette Haas; Thomas Rothe (European Regional Science Association (ERSA), 2006)
In the last years the analysis of flow figures turned out to be essential for labour market research and policy advice. The ongoing debate about how flexible is the German labour market could not been answered just analysing stock figures or turnover rates. Here we follow the useful analytical framework of transitional labour markets dealing centrally with flow figures. By developing a multi-account system (MAS) we go some steps ahead compared to indicators like job and labour turnover rates. First we combine the information of administrative data of the micro level with macro data containing pupils, self employed, retired persons. Embedded in an external framework, which is given by demography, the MAS describes the transition process of the labour market on the regional level and contains all 180 local employment agencies in Germany. The multi-account model thus serves as a basis for strategically aligning each agency with the individual local situation of the labour market by explicitly taking into account the regional specifics. Thus it helps for future strategic decisions of active labour market policy, which has been regionalized increasingly. For estimating the unknown transitions of the data matrix we use a new algorithm the so called ADETON tool, which has the additional merit comparing to other entropy maximizing methods, that constraints can be formulated in a fuzzy way rather than exactly. Further we demonstrate on the basis of three agencies (Ingolstadt, Memmingen, Halle) some practice and numerical examples concerning transitions from vocational training to the following labour market status. We state that the analytical potential of this instrument is not yet exhausted. In any event, it is already clear that the information content of this model by far exceeds that of a system of individual indicators. Details and relations of the regional labour market become apparent which show a high-resolution image of possible obsolete structures or increasing labour market dynamics. The model thus gives clear hints as to the scope and limits of the active labour market policy.
Keywords: 330